Comparative Study Of Probing Done with and without Endoscopic Assistance - Ishan Acharya; Jitendra Jethani; Monika Jethani (Delhi Journal of Ophthalmology)
Aims: The aims of our study were (1) to compare success of probing done blindly and probing done under endoscopic assistance (2) to correlate the findings of blind probing with endoscopic examination findings. Materials and Methods: Retrospective comparative interventional case study. Total 98 eyes of 84 children were included in the study. The probing was performed under brief inhalational anaesthesia with a laryngeal mask. All probings, secondary and in children older than 24 months, were performed under endoscopic assistance only. Results: Total 111 probings were done out of which, ninety-eight (88.29%) were primary and 13 (11.71%) secondary. Seventy-six (68.4%) probings were done without and thirty-five(31.53%) probings were done with nasal endoscopic assistance. Out of 35, 22 (19.81%) probings were primary and 13 (11.71%) secondary. The mean age for probing was 18.2 +/- 12.5 months. Thirty eight (45.23%) were females and 46 (54.77%) were males. Out of 76 primary probings, 13 (17.10%) probings failed. The mean age of failed primary probing was 15.2 +/- 6.7 months. All 22 primary probings done under endoscopic guidance had successful outcome. Out of the total 111 probings, 2 (1.80%) probings failed who underwent endonasal dacryocystorhinostomy in the same sitting. Conclusion: Use of simultaneous nasal endoscopy during probing increases the success rate, minimizes secondary procedures and isof prognostic value for children with Congenital nasolacrimal duct obstruction (CNLDO).